A simple, efficient, sensitive and practicability: Polyoxyphenylpropeone fluorescent probes for biological imaging. (December 2021) - Lian, Guangchang; Xiao, Fuyan; Hu, Kaibo; Wang, Yuling; Shao, Tingyu; Jin, Guofan
Abstract: A new type of polyoxyphenylpropeone fluorescent probe was designed by one pot method. In this article, through a simple synthetic route, a sensitive fluorescent probe for the detection of Fe 3+ and Cu 2+ in vitro was successfully synthesized. Interestingly, the fluorescence of this novel probe quenched significantly in the presence of Fe 3+ and Cu 2+ . Ketone carbonyl group and oxygen atom form the natural coordination site of iron ion and copper ion. After the coordination with metal ion, the conjugated system of the compound is broken, resulting in fluorescence quenching. At the same time, transmission electron microscope (TEM) were conducted to found its morphology property and the result shows that the polymer is stacked in layers in the images. The results of cell imaging confirmed that the polymer probe possessed favorable biocompatibility. The in vivo experiment of mice also gained the same conclusion with high penetration and fluorescence intensity. Due to the convenience of synthesis and superior recognition performance, this fluorescent probe has great potential in the study of accumulation and transformation of heavy metal ions in vivo and clinical detection of Fe 3+ and Cu 2+ . Graphical Abstract: ga1 Highlights: Synthesis of polyoxyphenylpropeone fluorescent probe by one-pot method. The polymer is highly responsive to Fe 3+ and Cu 2+, and its fluorescence is quenched prominently. The fluorescence emission band of polymer was observed at 600 nm in DMSO. Transmission electron microscope (TEM) results show the polymer molecules are stacked inside. Hela cell imaging experiments give a distinguishing intense fluorescence. The in vivo experiment of mice shows the excellent biocompatibility of the polymer.